2015
DOI: 10.1007/s11999-014-3840-2
|View full text |Cite
|
Sign up to set email alerts
|

The PROMIS Physical Function Correlates With the QuickDASH in Patients With Upper Extremity Illness

Abstract: Background To assess disability more efficiently with less burden on the patient, the National Institutes of Health has developed the Patient Reported Outcomes Measurement Information System (PROMIS) Physical Functionan instrument based on item response theory and using computer adaptive testing (CAT). Initially, upper and lower extremity disabilities were not separated and we were curious if the PROMIS Physical Function CAT could measure upper extremity disability and the Quick Disability of Arm, Shoulder and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
79
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 26 publications
7
79
1
1
Order By: Relevance
“…9,11,13,18,19 Menendez observed that 51% of variability in the qDASH was explained by differences in PROMIS PI CAT scores among new or follow-up hand surgery patients at an urban academic medical center, and furthermore reported a large correlation between PROMIS PI and qDASH scores and medium correlation between PROMIS depression CAT and qDASH scores. 19 Nota observed that pain interference had a strong influence on qDASH variability in a similar patient cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,11,13,18,19 Menendez observed that 51% of variability in the qDASH was explained by differences in PROMIS PI CAT scores among new or follow-up hand surgery patients at an urban academic medical center, and furthermore reported a large correlation between PROMIS PI and qDASH scores and medium correlation between PROMIS depression CAT and qDASH scores. 19 Nota observed that pain interference had a strong influence on qDASH variability in a similar patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…9,13 In a retrospective study of 93 consecutive new and follow-up outpatients, Overbeek observed that increasing PROMIS PI CAT scores were associated with greater disability on the PROMIS PF CAT and qDASH. 13 Similarly, Doring published data suggesting an association between the PROMIS UE and PI CATs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the Patient-Reported Outcomes Measurement Information System (PROMIS 1 ) Computer Adaptive Testing (CAT) measures, PROMIS 1 depression and PROMIS 1 pain interference (the degree to which pain interferes with activities of daily living) have been shown to be associated with disability as measured by the QuickDASH [11,21]. Social support has been found to be an independent predictor of pain outcomes among patients with chronic pain [17], and a target for psychosocial treatments in this population [13].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of anxiety and depression adversely affect outcomes scores in patients whose physical health status is objectively no worse [12,15]. While those symptoms can confound the use of otherwise valid patient-reported outcomes tools, they render the measurement of satisfaction with treatment outcomes all but impossible.…”
mentioning
confidence: 99%